Examining the interconnection between queer women's resistance and their social worlds in South Africa from 1980 to 2010 - Johnson, Kirsten (Department of Historical Studies, 2025)
This thesis examines how lesbian, bisexual, transgender and queer (LBTQ+) South African women were able to resist intersectional oppression through both their public activism and their intimate social worlds from 1980 to 2010 by analysing the webs of connection between the two. While queer historical literature has indicated there have been various forms of social exclusion and oppression both towards the LGBTQ+ community, and within the community itself, the experiences of women have been underexplored in this body of literature. The research draws on eleven in-depth interviews conducted with LBTQ+ individuals from around South Africa who at some point of their life identified as a woman and were involved in the LGBTQ+ liberation movement. It also includes rich material from the GALA Queer Archives. There are four major findings of this research. Firstly, women who were oppressed by religious institutions based on their sexual orientation experienced intrapersonal identity conflict and rejected either their religious identity or their sexual orientation prior to their negotiation and acceptance of their multiple identities. This reconciliation of identity led to situational compartmentalization or integration of their identities. Secondly, socialising with other LGBTQ+ individuals played an important role in helping queer women to cope with the emotional impact of their multifaceted oppression. Thirdly, the LGBTQ+ liberation movement successfully employed an array of tactics to utilise visibility as a strategy to ensure LGBTQ+ rights, most notably through the Pride Marches and the Out in Africa Film Festival. However, this tactic highlighted the fragmentation within the LGBTQ+ liberation movement due to racism and sexism. Lastly, this splintering led to the development of a more radical and feminist-oriented approach to LGBTQ+ liberation by black lesbian women. These findings are important as they document both queer women's experiences of intersectional oppression both within the LGBTQ+ movement and wider society and the ways in which they exercised agency, resilience, and community building.